2011
DOI: 10.1016/j.neuron.2011.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Action on GABAergic Neurons Prevents Obesity and Reduces Inhibitory Tone to POMC Neurons

Abstract: SUMMARY Leptin acts in the brain to prevent obesity. The underlying neurocircuitry responsible for this is poorly understood, in part due to incomplete knowledge regarding first order, leptin-responsive neurons. To address this, we and others have been removing leptin receptors from candidate first order neurons. While functionally relevant neurons have been identified, the observed effects have been small suggesting that most first order neurons remain unidentified. Here we take an alternative approach and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

40
1,057
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,117 publications
(1,148 citation statements)
references
References 78 publications
40
1,057
1
5
Order By: Relevance
“…The Vgat-ires-Cre triggered reexpression of RIIβ in the DMH, ARC, and LH, but not the VMH and PVH regions of the hypothalamus (Fig. 6A), as expected, because these latter areas are primarily composed of glutamatergic neurons (23,24). Reexpression of RIIβ is also strong in the striatum (Fig.…”
Section: Specific Riiβ Reexpression In Striatum Reverses the Hyperactsupporting
confidence: 76%
See 1 more Smart Citation
“…The Vgat-ires-Cre triggered reexpression of RIIβ in the DMH, ARC, and LH, but not the VMH and PVH regions of the hypothalamus (Fig. 6A), as expected, because these latter areas are primarily composed of glutamatergic neurons (23,24). Reexpression of RIIβ is also strong in the striatum (Fig.…”
Section: Specific Riiβ Reexpression In Striatum Reverses the Hyperactsupporting
confidence: 76%
“…The RIIβ reexpression studies described above implicate the hypothalamus as the site of the lean phenotype, but our efforts to pinpoint a specific cell type were unsuccessful. A recent study using a Vgat-ires-Cre to specifically eliminate the LepR demonstrated that LepRs in GABAergic inhibitory neurons are the key regulators of body weight (23). Using this Cre-expressing mouse line, we have reexpressed RIIβ only in GABAergic neurons to test whether this subset of neurons is responsible for the lean and hyperactive phenotypes of RIIβ KO mice.…”
Section: Specific Riiβ Reexpression In Striatum Reverses the Hyperactmentioning
confidence: 99%
“…In addition to the mice as described in chapter II, Slc17a6-ires-Cre (Vglut2-Cre) (Vong et al, 2011) (Jackson Labs stock 016963), Gad1-GFP (Δneo) (GAD67-GFP) (Tamamaki et al, 2003), and Slc32a1-ires-Cre (Vgat-Cre) (Vong et al, 2011) (Jackson Labs stock 016962) mice were used. In some optogenetic experiments, multiple behavioral tests were conducted in the same group of mice.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Less is known about how leptin affects other pathways including the GABAergic, glutamatergic, and dopaminergic systems (Scherer and Buettner, 2011;Vong et al, 2011).…”
mentioning
confidence: 99%
“…Understanding the dynamics and players involved in hypothalamic metabolism in obesity has been an elusive goal despite many decades of research, and is an intense area of current research (Koch et al, 2011;Scott et al, 2011;Vong et al, 2011;Williams and Schwartz, 2011). In the featured manuscript on neuroglial metabolic compartmentation underlying leptin deficiency in the obese ob/ob mice, Delgado et al (2011) used a multifaceted approach to study activity and metabolism in hypothalamic nuclei of control and ob/ob mice.…”
mentioning
confidence: 99%